Burnout and engagement in portuguese male military officers - Queirós, C. (2012)
Occupational stress is a contemporary concern due to its negative consequences in workers, especially when chronic, since it can provoke burnout (Freudenberger, 1974; Maslach, 1976). However, engagement is being identified as a possible protector of burnout and occupational stress (Schaufeli et al., 2002). Military officers have a dangerous and stressful activity, factor that is enhancing studies on burnout and engagement in this group (Alarcon et al., 2010; Chambel & Cruz, 2010; Ivie & Garland, 2011).